A Feasibility systems on green glass - Malapad, Leandro; Mendez, Faye Yvonne T.; Tobeza, Gene Mark M.; Parmis, Melisa A. (Diliman, Quezon City College of Engineering, 2013)
This study aims to assess the feasibility of Green Glass, a type of float glass of which the calcium oxide (CaO) component is obtained from seashells. It is an eco-friendly glass that is used as glass windows for residential homes and condominiums. Green Glass is made by the utilization of the optimal mixture of chemical compounds and glass cullet which yields its desired quality. For the first part of the study, the primary information regarding Green Glass is established. The product's competitive advantage and the possible competitors are determined. The demand for the general type of glass is analyzed and from that the specific use of glass that Green Glass will be venturing on is identified as well as the potential customers and the target market share. Different marketing strategies are also planned to introduce the Green Glass to the market Real estate developers and construction companies are targeted to be the primary market of Green Glass, a part of its strategy is joining in the bidding of glass contractors, partnership with environmental organizations, and participation in green environment campaigns. Approximately Php 500,000 will be needed for marketing Green Glass in the first year. Furthermore, the sales revenue for Green Glass in the first five years of its establishment is expected to be around Php 90 million. The projected demand for Green Glass is used to determine the amount of Green Glass to be produced in the next five years. As such, the minimum operating requirements were set up. This includes the identification and of the required number of machines and equipment to be used and the determination of the plant location. Key people for the start-up of the organization were also assigned. Based from the available data, a cost analysis was made to verify whether the project is still within the given budget An initial project cost of approximately Php 8.3 million is needed. Manufacturing, general, and administrative costs are identified, as well as the operating and investment costs. The sources of hinds for the company are planned, which will be sourced for debt and equity financing Financial statements are made to fully determine the feasibility of running the business and financial analysis are done to show that that business will be profitable. A net present value in 5 years of Green Glass has a positive value of Php 21,665,227.30, indicating that project is desirable at the specified rate. Also, the project has a 45.5% internal rate of return which also indicates that the project is acceptable. It is concluded that indeed, the Green Glass company Is financially feasible. Lastly, the social profitability study is done to determine if the business can contribute to the community and society. The benefit/cost ratio computed for Green Glass is approximately 2.51, which means that the project is socially profitable.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Participatory monitoring and evaluation (Project management); Glass manufacture; Silica, Vitreous